COGNITIVE ACADEMIC LANGUAGE LEARNING APPROACH (CALLA) TO PROMOTE READING COMPREHENSION – A PEDAGOGIC INTERVENTION TO ENGLISH FOR MATH CLASS B IN MATHEMATIC EDUCATION MAJOR OF UNKRISWINA SUMBA - Itha Priyastiti (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2019)
English for Academic Purposes (EAP) in university level requires students to have competence in contend-based English emphasizing in skills that are related to subject of study; thus, content-based instruction (CBI) is celebrated. However, prior to university level, students were taught general English, which does not address on specific skills of the language; thus, the requirement to facilitate university students with content-based learning has become a challenge both for students and teachers because of the gap between the previous learning experience and the expected skills. For that reason, an integrative approach is needed as a strategy to bridge the gap before the implementation of CBI. With the emphasis on fostering learning strategies, Cognitive Academic Language Learning Approach (CALLA) aimed as a modified adjunct model might be used as a “bridge” that help learners to be prepared to enter academic content area. Modifying CALLA syllabus using Quadrant III of Cummin’s Framework of Classification of Language and Content as guidance, this study investigated the effectiveness of the model in improving students’ reading comprehension ability. The result showed that CALLA improved students’ reading comprehension in the following sub skills: identifying details; identifying main ideas; identifying details; and inferring.